A novel inferior alveolar nerve block technique with enhanced success rate: A case series - Agarwal, Prateek; Gupta, Ritu (Journal of Case Reports in Dental Medicine, 2025)
Objective:This study aims to introduce and evaluate a novel technique for administering the inferior alveolar nerve block (IANB), which demonstrates a 100% success rate and improved anatomical landmark identification compared to conventional methods.Methods:A prospective clinical study was conducted at The Dental Door (Private clinic), India, involving 100 patients undergoing mandibular dental procedures. The newly proposed technique, characterized by simplified landmark identification and modified needle angulation, was employed. Success was defined by the onset of effective anaesthesia within 3–5 minutes without the need for re-injection. The results were compared with data from traditional IANB techniques performed in a matched historical cohort.Results:The novel technique demonstrated a 100% success rate, significantly higher than the 80–85% success rate typically reported with conventional IANB methods. None of the patients required re-injection, and anatomical landmarks were more consistently identifiable.Conclusion:This new IANB technique offers a highly effective and reproducible alternative to the conventional method, especially beneficial in busy clinical settings due to its ease of application and improved reliability.